The effect of money supply, interest rate, and exchange rate on inflation in Indonesia 2001-2013 - Sri Wulandari (Proceedings of AICS - Social Sciences, 2017)
This study aims to determine the effect of money supply, interest rate and exchange rate on inflation in Indonesia. Data analysis model used in this research is Multiple Regression Analysis Test. The data used are annual data from 2001 until 2013. The results show that the money supply, interest rate and exchange rate have an influence on inflation in Indonesia. From the results of processing showed R2 = 0.549 can be interpreted that the money supply, interest rate and exchange rate able to explain 54.9% inflation. While as much as 45.1% in influenced by other variables that are not included in the study.